Pengendalian Keselamatan Penerbangan Sebagai Upaya Penegakan Kedaulatan Negara di Ruang Udara dan Implikasinya di Indonesi - Yustitianingtyas, Levina; Babussalam, Basuki; Wijayanti, Asri (Jurnal Komunikasi Hukum, 2021)
The main concept that applies to the national airspace of a country is that the national airspace is closed to the flight of foreign aircraft. This is a further consequence of the acceptance of a state's complete and exclusive sovereignty over its air space. Therefore it is necessary to control the air space as one of the ways to enforce state sovereignty in air space. Even so, despite efforts to control air space, there are still frequent violations of Indonesian airspace. In writing this law, the focus of the problem to be studied is related to the occurrence of violations of a country's airspace if the foreign aircraft is in the Indonesian airspace without a permit or carries out flight activities not through a flight path that has been determined based on Indonesian national legislation as an effort to enforce sovereignty state in air space.